Competitive advantage through internal perception of organizational culture - Mohd Isa, Mohd Faizal; Zainal, Arifin; Abdul Aziz, Fazli Shah; Wan Mohd Noor, Wan Shakizah; Daud, Zulkiflee; Masnan, Maz Jamilah (2010)
Current business environment has become more complicated and advanced. Therefore, an organization should sustain its competitive advantage to ensure the business survival. An organization may enhance its business competitive advantage through their employees. This paper attempts to discuss relationship between the internal perceptions of organizational culture and strategic human resource management. A cross-sectional survey was performed to identify the current scenario of internal perception among 187 employees in Malaysian broadcasting industry. Research results showed that there were different means score in each dimension of the studied organizational culture and strategic human resource management.There exist significance correlations and regressions among the variables. The research findings suggest that the relationship between organizational culture and strategic human resource management influence the competitive advantage of the Malaysia broadcasting industry.